De verborgen estafette Hoe de kiembaan de generaties verbindt - Boer, Peter de (Radboud University Press, 2023)
Reproduction is an important central topic in biology. Reproduction genetics are at the heart of some of life's most basic questions such as: where do we come from, what are we and where are we going? Reproduction genetics connects current generations with past and future ones, and is intimately connected with fertility and infertility. The cellular lineage instrumental in the passage of life is called the germline while the mature functional products are the gametes. These form the main theme of this book. This book bridges the gap between existing textbooks and society by describing the germline as a passage in time. This book includes high quality illustrations, a complete glossary and references for each chapter, with the most prominent research highlighted. The interactions between the science of reproduction genetics and society are addressed. The text also includes personal experiences of the author from a 40-year career in the field. The book aims to combine knowledge and insight for an audience with some knowledge of the intertwined sciences of genetics and reproduction. The 'knowledge landscape' has been organised into 19 chapters. The book is aimed at those dealing with these subjects professionally, in education and elsewhere. It also has a lot to offer the educated layman thanks to the excellent illustrations and up-to-date glossary of scientific terms.